Alagille Syndrome Pathogenesis and Clinical Management (Springer International Publishing, 2018)
This text provides a concise yet comprehensive overview of Alagille syndrome. The book reviews the pathophysiology and genetics of the disorder, discusses recent molecular advances and its impact on diagnostics, and describes management challenges and strategies. The text also touches upon future treatment options. Written by experts in the field, Alagille Syndrome: Pathogenesis and Clinical Management is a valuable resource for physicians and researchers dealing with this disorder, one that will help guide patient management and stimulate investigative efforts. .